The Restrictiveness of Migration Policies in South Africa - SERGIO CARCIOTTO (African Journal of Governance and Development, 2021)
Political rhetoric and the migration-security nexus contribute to the widespread perception that migration policies have become more restrictive. Drawing on the DEMIG POLICY database, a large multi-country dataset, this paper assesses migration policy restrictiveness in South Africa over the period 1948 through 2020. Findings suggest that migration policies have become less restrictive and show how changes in policy restrictiveness vary according to the different policy areas and target groups. While policies of entry, stay and exit have turned towards less restrictiveness, border control policies have remained largely restrictive. Furthermore, while policy restrictions have affected asylum seekers and refugees, low-skilled migrant workers have benefited from amnesties and regularisation programmes. These short-term programmes raise a normative question about the socio-economic rights of those who are neither citizens nor long-term residents.